Sponge city ultra-flat wear-resistant concrete surface topcoat and preparation method thereof
By spraying a wear-resistant topcoat containing modified resin and graphene on sponge urban permeable bricks, the problem of insufficient compressive resistance and durability of permeable bricks is solved, and higher wear resistance and aesthetics are achieved. And reduce construction and environmental impacts.
Patent Information
- Application Number
- CN202311799084.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-12-25
AI Technical Summary
The existing sponge urban permeable bricks have shortcomings in compressive resistance and durability, especially when there are driving loads or large-area crowd loads, which affects the overall construction effect of the square.
A sponge urban ultra-flat wear-resistant concrete top coat is adopted, including water-based polyurethane-polyester fiber emulsion, modified ABS resin, polyvinyl alcoholate modified epoxy resin, graphene, inorganic filler, pigment, and other Coupling agents, tackifiers, leveling agents and curing agents form high toughness, weather resistance and wear resistance coatings through surface modification and chemical crosslinking, improving the durability and compressive resistance of permeable bricks.
It significantly improves the durability, compressibility and service life of permeable bricks, reduces the cement self-leveling layer during construction, enhances the wear resistance and decorative aesthetics of the concrete surface, and reduces the emission of harmful solvents, reducing Hazards to the environment and the human body.
Smart Images

Figure BDA0004628440030000131 
Figure BDA0004628440030000141
Abstract
Description
Technical Field
[0001] The invention relates to a sponge city ultra-flat wear-resistant concrete surface topcoat and a preparation method thereof, and specifically relates to the technical field of concrete surface protection, especially the construction of large-area public places such as squares that have sponge city construction needs. Background Art
[0002] At present, most urban square constructions still use dense and closed surface paving structures such as cement concrete and asphalt concrete to replace the original soil surface. Large-area public places such as open-air parking lots, courtyards and squares in cities are mostly paved with stone slabs or bricks such as granite. The dense pavement layer can only organize the surface runoff generated by rainfall into the urban drainage system through gravity drainage, and then discharge it into rivers, lakes and seas. Based on the above situation, when the precipitation is large, there is too much surface water. If it cannot be discharged into the urban drainage system in time or exceeds the load of the urban drainage system, it will bring inconvenience and safety hazards to pedestrians and vehicles, and even cause urban waterlogging disasters.
[0003] For this reason, China has begun to vigorously promote the application of sponge facilities such as permeable paving. At present, most permeable paving in the technology is permeable by increasing the porosity of the paving material or by setting multiple water-conducting holes. The patent document with publication number CN110904762A discloses a permeable brick for sponge city, but the cavity set inside the brick material causes the pavement to have poor compressive resistance. For venues with vehicle loads or large crowd loads, it is easy to break and loosen under the action of external forces, affecting the overall construction effect of the square. At present, sponge transformation mostly adds water storage modules to its structural layer or uses permeable paving on the surface layer. In order to improve the durability of ground permeable bricks, a layer of wear-resistant topcoat is currently sprayed on the surface layer of the permeable bricks to protect the permeable bricks, thereby improving the durability, compressive resistance and service life of the permeable structure.
[0004] In view of the current technical problems, the sponge transformation of the square, as the core point in the construction of the sponge city, urgently needs to prepare a topcoat that can improve the durability of the permeable brick surface. Summary of the invention
[0005] In view of the problems of the prior art, the present invention provides a sponge city ultra-flat wear-resistant concrete surface topcoat and a preparation method thereof. The topcoat prepared by the present invention has the characteristics of durability, wear resistance, high toughness and good weather resistance, and is suitable for the central permeable brick surface layer of urban construction. Pigments are also added to the topcoat, which can have a certain protective effect and decorative effect.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A sponge city ultra-flat wear-resistant concrete surface topcoat, the topcoat comprising the following raw materials in parts by weight:
[0008] 30-50 parts by weight of aqueous polyurethane-polyester fiber emulsion, 20-30 parts by weight of modified ABS resin, 30-50 parts by weight of polyvinyl alcohol ester modified epoxy resin, 5-10 parts by weight of graphene, 3-5 parts by weight of inorganic filler, 3-5 parts by weight of pigment, 1-3 parts by weight of coupling agent, 1-3 parts by weight of tackifier, 0.5-2 parts by weight of leveling agent, 0.5-1 parts by weight of curing agent and 30-40 parts by weight of solvent;
[0009] Wherein, the graphene is graphene that has undergone surface modification treatment, and the solvent is ethanol.
[0010] In particular, graphene has excellent mechanical properties and a special two-dimensional structure, which can improve the microstructure of building materials. Graphene after surface modification can further improve its compatibility with resin materials and improve the mechanical properties and durability of the materials. The addition of graphene brings intelligent functions such as structural damage and stress-strain self-diagnosis to the material, which can monitor the health status of the building structure in real time, promptly discover potential safety hazards, and provide strong support for the maintenance and reinforcement of the building structure, thereby improving the strength, stability, impact resistance and durability of the material.
[0011] Wherein, the preparation method of the aqueous polyurethane-polyester fiber emulsion comprises the following steps:
[0012] Add polyester fiber and polyurethane powder into a stirring device, add ethanol, heat to 70-80°C, stir to fully dissolve, add plasticizer, continue stirring until the solution becomes uniform and transparent, then stir and shake the mixed solution to remove bubbles in the solution to obtain a water-based polyurethane-polyester fiber emulsion.
[0013] In particular, the plasticizer includes at least one of epoxy soybean oil, tributyl phosphate, stearyl glyceride, p-toluenesulfonic acid amide and cyclobutane acid ester, preferably epoxy soybean oil plasticizer. Epoxidized soybean oil has good weather resistance and low volatility, and has a good compatibility with waterborne polyurethane, so that the waterborne polyurethane and polyester fiber are mixed more evenly, the prepared product is more durable, the service life is extended, and the harm to human health and the environment is less.
[0014] The preparation method of the modified ABS resin comprises the following steps:
[0015] Step 1: Add the dried glass fiber nanoparticles into a stirring device of the polyethylene glycol ethanol solution, heat to 50-60° C., mix and stir for 1-3 hours, filter, and dry to obtain modified glass fibers;
[0016] Step 2: Add the modified glass fiber to the ethanol solution of ABS resin, stir and mix evenly, heat to 70-80°C, keep reacting for 1-3h, then add the ethanol solution of silane coupling agent KH-550, continue stirring, heat to 70-80°C, keep reacting for 3-5h, after the reaction is completed, add buffer solution to adjust the reaction pH, filter, and obtain modified ABS resin.
[0017] In particular, nano-scale modified glass fibers are used to modify the surface of ABS resin. The surface structure of the modified glass fibers changes, and under the synergistic effect of silane coupling agents, the modified glass fibers have better compatibility with ABS resin, making the mixing more uniform under stirring to form a uniform and dense interface layer. The excellent properties of the two are combined to make the prepared topcoat have high toughness, fatigue resistance and durability. A 5% sodium hydroxide solution is used as a buffer solution to adjust the pH of the solution to neutral, which further improves the stability of the topcoat performance.
[0018] The preparation method of the polyvinyl alcohol ester modified epoxy resin comprises the following steps:
[0019] The epoxy resin treated with epoxy silicone and the ground polyvinyl alcohol ester are mixed in proportion, a catalyst and a diluent are added, the mixture is stirred evenly, and the mixture is heated to 80-100°C and kept reacting for 3-5 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, dried, ground, and sieved to obtain a polyvinyl alcohol ester modified epoxy resin; wherein the mesh size of the sieve is 300-400 meshes.
[0020] In particular, the catalyst is preferably butyl titanate in the organic titanium catalyst, and the diluent is preferably acetone. The organic titanium catalyst is selected because it has high reactivity and selectivity, increases the polymerization rate of polyvinyl alcohol ester and epoxy resin, shortens the reaction time, and selects acetone with good solubility as the reaction diluent, which greatly improves the reaction efficiency.
[0021] Furthermore, polyvinyl alcohol ester has excellent elasticity, cold resistance, heat resistance, chemical corrosion resistance and other characteristics. It is combined and modified with epoxy resin through chemical reaction, which improves the processing performance of epoxy resin, improves its fluidity and dispersibility, and also improves the toughness, toughness and weather resistance of epoxy resin. Polyvinyl alcohol ester can also react with other resin components in the topcoat to form a stable cross-linked structure, thereby improving the curing degree and heat resistance of the topcoat, so that it maintains good performance in high temperature environment, and improves stability and durability as a whole.
[0022] In particular, the inorganic filler includes at least one of quartz sand, calcium carbonate, molecular sieve powder, talcum powder, carbon fiber, glass fiber and wollastonite powder, preferably quartz sand. Quartz sand has high hardness and good chemical stability. Adding it to the preparation of the material can enhance the wear resistance and durability of the topcoat and extend the service life of the concrete structure. In addition, quartz sand is low in price and can reduce costs.
[0023] In particular, the pigment includes at least one of iron oxide red, mica iron oxide, carbon black, zinc yellow, iron titanium powder, zinc phosphate and mica pearl powder, preferably mica pearl powder. Mica pearl powder is a pigment with unique luster and color, which can give the concrete protective layer topcoat a pearl-like luster and texture, which can improve the decorativeness and durability of the concrete surface, so that it can remain beautiful and durable in various environments. Mica pearl powder also has excellent weather resistance and chemical resistance, can resist the erosion of external factors such as ultraviolet rays and chemicals, and thus prolong the service life of the concrete protective layer topcoat. And mica pearl powder can emit light autonomously at night, has certain decorativeness and environmental protection, can save energy, and can protect buildings.
[0024] In particular, the tackifier includes at least one of hydroxyethyl methylcellulose, montmorillonite, lithium stearate, petroleum resin, alkylphenol-formaldehyde resin, polymethylstyrene resin, polydimethylsiloxane, ketone-aldehyde resin and xylene formaldehyde resin, preferably polydimethylsiloxane. The addition of polydimethylsiloxane can improve the bonding force between the topcoat and the concrete surface, making it more firmly attached to the concrete surface, improving the water resistance, weather resistance and chemical resistance of the topcoat, and extending the service life of the topcoat of the concrete protective layer.
[0025] The coupling agent includes at least one of monoalkoxy titanate, chelate titanate, epoxy silane, mercapto silane and amino silane.
[0026] In particular, the leveling agent includes at least one of acrylic emulsion, polyether siloxane and polyether modified silicone oil, preferably polyether siloxane. Polyether siloxane as a leveling agent can improve the fluidity and wettability of the topcoat during the construction process, so that the topcoat can be better covered on the concrete surface, improve the coating effect and uniformity of the coating, and polyether siloxane can also improve the scratch resistance and orange peel resistance of the topcoat, thereby extending the service life of the concrete protective topcoat.
[0027] In particular, the curing agent includes at least one of polyisocyanate type, polyurethane type and amino resin type, preferably polyisocyanate curing agent. Polyisocyanate has good compatibility with polyurethane and other resins in the material, forms a resin material with a three-dimensional structure through chemical cross-linking, and reacts on the concrete surface layer to form a high-strength polyurethane coating, thereby improving the hardness, toughness and impact resistance of the concrete surface layer, and also improving the durability of the topcoat and extending the service life of the topcoat.
[0028] A method for preparing a sponge city ultra-flat wear-resistant concrete surface topcoat, the preparation method of the topcoat is as follows:
[0029] S1. Add waterborne polyurethane-polyester fiber emulsion, modified ABS resin and polyvinyl alcohol ester into a container at room temperature, control the rotation speed to 500-700 rpm, and keep stirring for 15-30 minutes to obtain a mixed solution A;
[0030] S2. Add graphene, inorganic filler, coupling agent, tackifier, leveling agent and ethanol to the mixed solution A in parts by weight, control the rotation speed to 600-1000 rpm, raise the temperature to 80-120° C., and keep stirring for 30-60 min to obtain a mixed solution B;
[0031] S3, after the stirring is completed, the rotation speed is increased to 1000-2000 rpm, pigment and curing agent are added to the mixed solution B, stirring is continued for 30-60 minutes, and a solvent is added to adjust the viscosity to the desired viscosity to obtain a topcoat. Beneficial effects of the present invention:
[0032] Compared with the prior art, in order to improve the durability of the permeable bricks on the ground, the present invention adopts the method of spraying a layer of wear-resistant topcoat on the surface of the permeable bricks to protect the permeable bricks, thereby improving the durability, compression resistance and service life of the permeable structure. By adjusting the color of the topcoat, the landscape effect that is difficult to achieve with the traditional paving brick surface can be achieved, and the aesthetics can be improved. At the same time, the topcoat combined with triple modified wear-resistant materials can further improve the durability of the site. The topcoat prepared by the present invention does not require a cement self-leveling layer, which reduces the load on the ground and speeds up the construction progress. In addition, the prepared topcoat has excellent wear resistance, can withstand heavy pressure, and vehicles can drive on the surface. All raw materials and auxiliary materials used to prepare the topcoat do not contain harmful solvents, reduce VOC emissions, and reduce harm to the human body and the environment. DETAILED DESCRIPTION
[0033] In order to further explain the technical means and effects taken by the present invention to achieve the predetermined invention purpose, the specific implementation methods, features and effects of the present invention are described in detail below in conjunction with the embodiments. The reagents and materials used in the present invention can be purchased from the market or prepared synthetically.
[0034] Example 1
[0035] A sponge city ultra-flat wear-resistant concrete surface topcoat, the topcoat comprising the following raw materials in parts by weight:
[0036] 30 parts by weight of aqueous polyurethane-polyester fiber emulsion, 20 parts by weight of modified ABS resin, 30 parts by weight of polyvinyl alcohol ester modified epoxy resin, 10 parts by weight of graphene, 5 parts by weight of inorganic filler, 3 parts by weight of pigment, 1 part by weight of coupling agent, 1 part by weight of tackifier, 0.5 parts by weight of leveling agent, 0.5 parts by weight of curing agent and 30 parts by weight of solvent;
[0037] The graphene is graphene that has been surface-modified, and the solvent is ethanol.
[0038] Among them, the inorganic filler is quartz sand; the pigment is mica pearl powder; the coupling agent is epoxy silane; the tackifier is polydimethylsiloxane; the leveling agent is polyether siloxane; and the curing agent is polyisocyanate.
[0039] The preparation method of the aqueous polyurethane-polyester fiber emulsion comprises the following steps:
[0040] Add polyester fiber and polyurethane powder into a stirring device, add ethanol, heat to 80°C, stir to fully dissolve, add epoxy soybean oil plasticizer, continue stirring until the solution becomes uniform and transparent, then stir and shake the mixed solution for degassing to remove bubbles in the solution to obtain a water-based polyurethane-polyester fiber emulsion.
[0041] The preparation method of the modified ABS resin comprises the following steps:
[0042] Step 1: adding the dried glass fiber nanoparticles into a stirring device of the polyethylene glycol ethanol solution, heating to 60° C., mixing and stirring for 3 hours, filtering, and drying to obtain modified glass fibers;
[0043] Step 2: Add the modified glass fiber to the ethanol solution of ABS resin, stir and mix evenly, heat to 70°C, keep reacting for 2.5 hours, then add the ethanol solution of silane coupling agent KH-550, continue stirring, heat to 80°C, keep reacting for 5 hours, after the reaction is completed, add 5% sodium hydroxide solution to adjust the reaction pH to 7.0, filter, and obtain modified ABS resin.
[0044] The preparation method of the polyvinyl alcohol ester modified epoxy resin comprises the following steps:
[0045] The epoxy resin treated with epoxy silicone and the ground polyvinyl alcohol ester are mixed in proportion, and butyl titanate and acetone are added. The mixture is stirred evenly, heated to 100°C, and the reaction is maintained for 3.5 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, dried, ground, and sieved through a 400-mesh sieve to obtain polyvinyl alcohol ester-modified epoxy resin.
[0046] A method for preparing a sponge city ultra-flat wear-resistant concrete surface topcoat, the preparation method of the topcoat is as follows:
[0047] S1. Add waterborne polyurethane-polyester fiber emulsion, modified ABS resin and polyvinyl alcohol ester into a container at room temperature, control the rotation speed to 700 rpm, and keep stirring for 20 minutes to obtain a mixed solution A;
[0048] S2. Add graphene, inorganic filler, coupling agent, tackifier, leveling agent and ethanol to the mixed solution A in parts by weight, control the rotation speed to 1000 rpm, raise the temperature to 120° C., and keep stirring for 50 min to obtain a mixed solution B;
[0049] S3. After the stirring is completed, the rotation speed is increased to 2000 rpm, and the pigment and curing agent are added to the mixed liquid B. The stirring is maintained for 40 minutes, and ethanol is added to adjust the viscosity to the required viscosity to obtain a topcoat.
[0050] Example 2
[0051] A sponge city ultra-flat wear-resistant concrete surface topcoat, the topcoat comprising the following raw materials in parts by weight:
[0052] 40 parts by weight of aqueous polyurethane-polyester fiber emulsion, 25 parts by weight of modified ABS resin, 40 parts by weight of polyvinyl alcohol ester modified epoxy resin, 10 parts by weight of graphene, 5 parts by weight of inorganic filler, 3 parts by weight of pigment, 1 part by weight of coupling agent, 1 part by weight of tackifier, 0.5 parts by weight of leveling agent, 0.5 parts by weight of curing agent and 35 parts by weight of solvent;
[0053] Wherein, the graphene is graphene that has undergone surface modification treatment, and the solvent is ethanol.
[0054] Among them, the inorganic filler is quartz sand; the pigment is mica pearl powder; the coupling agent is epoxy silane; the tackifier is polydimethylsiloxane; the leveling agent is polyether siloxane; and the curing agent is polyisocyanate.
[0055] The preparation method of the aqueous polyurethane-polyester fiber emulsion comprises the following steps:
[0056] Add polyester fiber and polyurethane powder into a stirring device, add ethanol, heat to 80°C, stir to fully dissolve, add epoxy soybean oil plasticizer, continue stirring until the solution becomes uniform and transparent, then stir and shake the mixed solution for degassing to remove bubbles in the solution to obtain a water-based polyurethane-polyester fiber emulsion.
[0057] The preparation method of the modified ABS resin comprises the following steps:
[0058] Step 1: adding the dried glass fiber nanoparticles into a stirring device of the polyethylene glycol ethanol solution, heating to 60° C., mixing and stirring for 3 hours, filtering, and drying to obtain modified glass fibers;
[0059] Step 2: Add the modified glass fiber to the ethanol solution of ABS resin, stir and mix evenly, heat to 70°C, keep reacting for 2.5 hours, then add the ethanol solution of silane coupling agent KH-550, continue stirring, heat to 80°C, keep reacting for 5 hours, after the reaction is completed, add 5% sodium hydroxide solution to adjust the reaction pH to 7.0, filter, and obtain modified ABS resin.
[0060] The preparation method of the polyvinyl alcohol ester modified epoxy resin comprises the following steps:
[0061] The epoxy resin treated with epoxy silicone and the ground polyvinyl alcohol ester are mixed in proportion, and butyl titanate and acetone are added. The mixture is stirred evenly, heated to 100°C, and the reaction is maintained for 3.5 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, dried, ground, and sieved through a 400-mesh sieve to obtain polyvinyl alcohol ester-modified epoxy resin.
[0062] A method for preparing a sponge city ultra-flat wear-resistant concrete surface topcoat, the preparation method of the topcoat is as follows:
[0063] S1. Add waterborne polyurethane-polyester fiber emulsion, modified ABS resin and polyvinyl alcohol ester into a container at room temperature, control the rotation speed to 700 rpm, and keep stirring for 20 minutes to obtain a mixed solution A;
[0064] S2. Add graphene, inorganic filler, coupling agent, tackifier, leveling agent and ethanol to the mixed solution A in parts by weight, control the rotation speed to 1000 rpm, raise the temperature to 120° C., and keep stirring for 50 min to obtain a mixed solution B;
[0065] S3. After the stirring is completed, the rotation speed is increased to 2000 rpm, and the pigment and curing agent are added to the mixed liquid B. The stirring is maintained for 40 minutes, and ethanol is added to adjust the viscosity to the required viscosity to obtain a topcoat.
[0066] Example 3
[0067] A sponge city ultra-flat wear-resistant concrete surface topcoat, the topcoat comprising the following raw materials in parts by weight:
[0068] 50 parts by weight of aqueous polyurethane-polyester fiber emulsion, 30 parts by weight of modified ABS resin, 50 parts by weight of polyvinyl alcohol ester modified epoxy resin, 10 parts by weight of graphene, 5 parts by weight of inorganic filler, 3 parts by weight of pigment, 1 part by weight of coupling agent, 1 part by weight of tackifier, 0.5 parts by weight of leveling agent, 0.5 parts by weight of curing agent and 40 parts by weight of solvent;
[0069] Wherein, the graphene is graphene that has undergone surface modification treatment, and the solvent is ethanol.
[0070] Among them, the inorganic filler is quartz sand; the pigment is mica pearl powder; the coupling agent is epoxy silane; the tackifier is polydimethylsiloxane; the leveling agent is polyether siloxane; and the curing agent is polyisocyanate.
[0071] The preparation method of the aqueous polyurethane-polyester fiber emulsion comprises the following steps:
[0072] Add polyester fiber and polyurethane powder into a stirring device, add ethanol, heat to 80°C, stir to fully dissolve, add epoxy soybean oil plasticizer, continue stirring until the solution becomes uniform and transparent, then stir and shake the mixed solution for degassing to remove bubbles in the solution to obtain a water-based polyurethane-polyester fiber emulsion.
[0073] The preparation method of the modified ABS resin comprises the following steps:
[0074] Step 1: adding the dried glass fiber nanoparticles into a stirring device of the polyethylene glycol ethanol solution, heating to 60° C., mixing and stirring for 3 hours, filtering, and drying to obtain modified glass fibers;
[0075] Step 2: Add the modified glass fiber to the ethanol solution of ABS resin, stir and mix evenly, heat to 70°C, keep reacting for 2.5 hours, then add the ethanol solution of silane coupling agent KH-550, continue stirring, heat to 80°C, keep reacting for 5 hours, after the reaction is completed, add 5% sodium hydroxide solution to adjust the reaction pH to 7.0, filter, and obtain modified ABS resin.
[0076] The preparation method of the polyvinyl alcohol ester modified epoxy resin comprises the following steps:
[0077] The epoxy resin treated with epoxy silicone and the ground polyvinyl alcohol ester are mixed in proportion, and butyl titanate and acetone are added. The mixture is stirred evenly, heated to 100°C, and the reaction is maintained for 3.5 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, dried, ground, and sieved through a 400-mesh sieve to obtain polyvinyl alcohol ester-modified epoxy resin.
[0078] A method for preparing a sponge city ultra-flat wear-resistant concrete surface topcoat, the preparation method of the topcoat is as follows:
[0079] S1. Add waterborne polyurethane-polyester fiber emulsion, modified ABS resin and polyvinyl alcohol ester into a container at room temperature, control the rotation speed to 700 rpm, and keep stirring for 20 minutes to obtain a mixed solution A;
[0080] S2. Add graphene, inorganic filler, coupling agent, tackifier, leveling agent and ethanol to the mixed solution A in parts by weight, control the rotation speed to 1000 rpm, raise the temperature to 120° C., and keep stirring for 50 min to obtain a mixed solution B;
[0081] S3. After the stirring is completed, the rotation speed is increased to 2000 rpm, and the pigment and curing agent are added to the mixed liquid B. The stirring is maintained for 40 minutes, and ethanol is added to adjust the viscosity to the required viscosity to obtain a topcoat.
[0082] Comparative Example 1
[0083] Compared with Example 1, the difference of Comparative Example 1 is that graphene without surface treatment is added in Comparative Example 1.
[0084] Comparative Example 2
[0085] Compared with Example 1, the difference of Comparative Example 2 is that in Comparative Example 2, the aqueous polyurethane-polyester fiber emulsion is replaced by an aqueous polyurethane emulsion.
[0086] Comparative Example 3
[0087] Compared with Example 1, the difference of Comparative Example 3 is that in Comparative Example 3, the aqueous polyurethane-polyester fiber emulsion is replaced by an aqueous polyester fiber emulsion.
[0088] Comparative Example 4
[0089] Compared with Example 1, the difference of Comparative Example 4 is that no aqueous polyurethane-polyester fiber emulsion is added in Comparative Example 4.
[0090] Comparative Example 5
[0091] Compared with Example 1, the difference of Comparative Example 5 is that in Comparative Example 5, the modified ABS resin is replaced by modified glass fiber.
[0092] Comparative Example 6
[0093] Compared with Example 1, the difference of Comparative Example 6 is that the modified ABS resin is replaced by glass fiber in Comparative Example 6.
[0094] Comparative Example 7
[0095] Compared with Example 1, the difference of Comparative Example 7 is that the modified ABS resin is replaced by modified ABS resin in Comparative Example 7.
[0096] Comparative Example 8
[0097] Compared with Example 1, the difference of Comparative Example 8 is that the modified ABS resin is replaced by ABS resin in Comparative Example 8.
[0098] Comparative Example 9
[0099] Compared with Example 1, the difference of Comparative Example 9 is that no modified ABS resin is added in Comparative Example 9.
[0100] Comparative Example 10
[0101] Compared with Example 1, the difference of Comparative Example 10 is that in Comparative Example 10, the polyvinyl alcohol ester-modified epoxy resin is replaced by polyvinyl alcohol ester.
[0102] Comparative Example 11
[0103] Compared with Example 1, the difference of Comparative Example 11 is that in Comparative Example 11, the polyvinyl alcohol ester modified epoxy resin is replaced by epoxy resin.
[0104] Comparative Example 12
[0105] Compared with Example 1, the difference of Comparative Example 12 is that no polyvinyl alcohol ester-modified epoxy resin is added in Comparative Example 12.
[0106] The topcoats prepared in Examples 1-3 and Comparative Examples 1-12 were subjected to relevant performance tests, and all test results are recorded in the following Table 1. The compressive strength test was conducted according to GB / T 32987-2016, the flexural strength, anti-slip and water resistance tests were conducted according to GB / T 25993-2010, and the adhesion, stain resistance and aging resistance tests were conducted according to the national standard GB / T 9755-2001 for synthetic resin emulsion exterior wall coatings.
[0107] Table 1 Test results of the finish paint properties prepared by Examples 1-3 and Comparative Examples 1-12
[0108]
[0109]
[0110] By analyzing the data in Table 1, the samples prepared in Examples 1-3 meet the requirements in the tests of compression resistance, flexural strength, anti-slip and water resistance, as well as adhesion, stain resistance and aging resistance, and the component ratio of Example 2 is the best experimental condition for preparing the topcoat. Comparative Examples 1-12 are modified materials. When only inorganic fillers or modified polymers are added, the relevant properties of the prepared topcoat are relatively reduced, but when no modified materials are added, the performance of the prepared topcoat does not meet the requirements. This may be caused by uneven mixing and stirring when preparing the topcoat in the case of only a single material component, resulting in uneven paint film.
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A sponge city ultra-flat wear-resistant concrete surface topcoat, characterized by: The topcoat comprises the following raw materials in parts by weight: 30-50 parts by weight of waterborne polyurethane-polyester fiber emulsion, 20-30 parts by weight of modified ABS resin, 30-50 parts by weight of polyvinyl alcohol ester modified epoxy resin, 5-10 parts by weight of graphene, 3-5 parts by weight of inorganic filler, 3-5 parts by weight of pigment, 1-3 parts by weight of coupling agent, 1-3 parts by weight of tackifier, 0.5-2 parts by weight of leveling agent, 0.5-1 parts by weight of curing agent and 30-40 parts by weight of solvent; Wherein, the graphene is graphene that has undergone surface modification treatment; The preparation method of the modified ABS resin comprises the following steps: Step 1: Add the dried glass fiber nanoparticles into a stirring device of the polyethylene glycol ethanol solution, heat to 50-60° C., mix and stir for 1-3 hours, filter, and dry to obtain modified glass fibers; Step 2: Add the modified glass fiber to the ethanol solution of ABS resin, stir and mix evenly, heat to 70-80°C, keep reacting for 1-3h, then add the ethanol solution of silane coupling agent KH-550, continue stirring, heat to 70-80°C, keep reacting for 3-5h, after the reaction is completed, add buffer solution to adjust the reaction pH, filter, and obtain modified ABS resin.
2. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The preparation method of the aqueous polyurethane-polyester fiber emulsion comprises the following steps: Add polyester fiber and polyurethane powder into a stirring device, add ethanol, heat to 70-80°C, stir to fully dissolve, add plasticizer, continue stirring until the solution becomes uniform and transparent, then stir and shake the mixed solution to remove bubbles in the solution to obtain a water-based polyurethane-polyester fiber emulsion.
3. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 2 is characterized by: The plasticizer includes at least one of epoxidized soybean oil, tributyl phosphate, stearyl glycerol, p-toluenesulfonic acid amide and cyclobutane acid ester.
4. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The buffer solution is a 5% sodium hydroxide solution, and the pH value is 7.5-8.
5. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The preparation method of the polyvinyl alcohol ester modified epoxy resin comprises the following steps: The epoxy resin treated with epoxy silicone and the ground polyvinyl alcohol ester are mixed in proportion, a catalyst and a diluent are added, the mixture is stirred evenly, and the mixture is heated to 80-100°C and the reaction is maintained for 3-5 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, dried, ground, and sieved to obtain the polyvinyl alcohol ester modified epoxy resin.
6. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The inorganic filler includes at least one of quartz sand, calcium carbonate, molecular sieve powder, talcum powder, carbon fiber, glass fiber and wollastonite powder; the pigment includes at least one of iron red, mica iron oxide, carbon black, zinc yellow, iron titanium powder, zinc phosphate and mica pearlescent powder.
7. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The tackifier includes at least one of hydroxyethyl methylcellulose, montmorillonite, lithium stearate, petroleum resin, alkyl phenolic resin, polymethyl styrene resin, polydimethylsiloxane, ketone-aldehyde resin and xylene formaldehyde resin; the coupling agent includes at least one of monoalkoxy titanate, chelate titanate, epoxy silane, mercapto silane and amino silane.
8. The sponge city super-flat wear-resistant concrete surface topcoat according to claim 1 is characterized by: The leveling agent includes at least one of acrylic ester emulsion, polyether siloxane and polyether modified silicone oil; the curing agent includes at least one of polyisocyanate type, polyurethane type and amino resin type.
9. A method for preparing a sponge city super-flat wear-resistant concrete surface topcoat according to any one of claims 1 to 8, characterized in that: The preparation method of the finish paint is as follows: S1. Add waterborne polyurethane-polyester fiber emulsion, modified ABS resin and polyvinyl alcohol ester modified epoxy resin into a container at room temperature, control the rotation speed to 500-700 rpm, keep stirring for 15-30 minutes, and obtain a mixed solution A; S2. Add graphene, inorganic filler, coupling agent, tackifier, leveling agent and solvent to mixed solution A in parts by weight, control the rotation speed to 600-1000 rpm, raise the temperature to 80-120° C., and keep stirring for 30-60 min to obtain mixed solution B; S3. After the stirring is completed, the rotation speed is increased to 1000-2000 rpm, pigment and curing agent are added to the mixed solution B, stirring is continued for 30-60 minutes, and a solvent is added to adjust the viscosity to the required viscosity to obtain a topcoat.